Fluorescent graphene quantum dots as traceable, pH-sensitive drug delivery systems - Qiu J (Dove Medical Press, 2015)
Jichuan Qiu,1 Ruibin Zhang,2 Jianhua Li,1 Yuanhua Sang,1 Wei Tang,3 Pilar Rivera Gil,4 Hong Liu1,51Center of Bio and Micro/Nano Functional Materials, State Key Laboratory of Crystal Materials, Shandong University, 2Blood Purification Center, Jinan Central Hospital, 3Department of Pathogenic Biology, Shandong University School of Medicine, Jinan, People’s Republic of China; 4Institute of Chemistry, Rovira i Virgili University, Tarragona, Spain; 5Beijing Institute of Nanoenergy and Nanosystems, Chinese Academy of Sciences, Beijing, People’s Republic of ChinaAbstract: Graphene quantum dots (GQDs) were rationally fabricated as a traceable drug delivery system for the targeted, pH-sensitive delivery of a chemotherapeutic drug into cancer cells. The GQDs served as fluorescent carriers for a well-known anticancer drug, doxorubicin (Dox). The whole system has the capacity for simultaneous tracking of the carrier and of drug release. Dox release is triggered upon acidification of the intracellular vesicles, where the carriers are located after their uptake by cancer cells. Further functionalization of the loaded carriers with targeting moieties such as arginine-glycine-aspartic acid (RGD) peptides enhanced their uptake by cancer cells. DU-145 and PC-3 human prostate cancer cell lines were used to evaluate the anticancer ability of Dox-loaded RGD-modified GQDs (Dox-RGD-GQDs). The results demonstrated the feasibility of using GQDs as traceable drug delivery systems with the ability for the pH-triggered delivery of drugs into target cells.Keywords: graphene quantum dots, drug delivery, pH-sensitive, controlled release, traceable